Impact of primary production and net ecosystem metabolism on carbon and nutrient cycling at the land-sea interface - Rewrie, Louise C. V.; Baschek, Burkard; van Beusekom, Justus E. E.; Körtzinger, Arne; Petersen, Wilhelm; Röttgers, Rüdiger; Voynova, Yoana G. (Frontiers in Marine Science, 2025)
Estuaries are typically net heterotrophic systems and a source of CO2 to the atmosphere, while continental shelves are net CO2 sinks. Yet, primary production and net ecosystem metabolism (NEM) are variable, and this has implications for nutrient and carbon processing along the land-sea interface. To resolve this variability, high-frequency dissolved oxygen and ancillary biogeochemical data from a research station (FerryBox) located at the outflow of a temperate estuary into a shelf sea, were used to quantify the gross primary production (GPP) and NEM at the land-sea interface. In early and mid-spring in the outer Elbe Estuary (Germany), we find that low GPP rates (155 ± 46 mg C m-2 d-1 in April 2020 and 74 ± 24 mg C m-2 d-1 in March to April 2021) were light limited, as a function of elevated turbidity (31 ± 9 NTU and 35 ± 7 NTU) and solar irradiance. When turbidity decreased in late spring (May), we observed elevated GPP rates, and highest GPP rates in summer (June-August), with seasonal averages of 613 ± 89 mg C m-2 d-1 in 2020 and 558 ± 77 mg C m-2 d-1 in 2021. Primary production in the outer Elbe Estuary waters was not nutrient-limited, since concentrations all year-round exceeded the expected limiting levels of 5 µM Si, 0.5 µM PO43- and 2 µM NO3-. Despite the high nutrient concentrations and estimated GPP rates, the system was in near trophic balance, with seasonally averaged NEM estimates of -2 ± 49 mg C m-2 d-1 and -149 ± 41 mg C m-2 d-1. A significant finding is that a seasonal decrease in dissolved inorganic carbon of 125 – 160 µmol kg-1 from May to September, and in total alkalinity of 116 – 128 µmol kg-1 from December to August, was likely driven by the concurrent and significant seasonal uptake of inorganic carbon by primary producers in the upper estuary and upstream regions. This highlights the heterogeneity of inorganic carbon patterns along the land-sea continuum and the continuity of biogeochemical processing in the upstream regions of a temperate estuary to sea.